補救教學中個別化教學對學生學習成效之影響分析 Impact of Individualized Instruction on the Learning Outcomes of Low-Achieving Students Who Received Remedial Instruction - 余民寧 Min-Ning Yu; 李昭鋆 Chao-Yun Li (National Taiwan Normal University, 2018)
本研究運用結構方程式模型中的中介模型，探索個別化教學透過自我歸因、學習動機等因素，對補救教學學習成效之影響關係的探討；樣本乃抽取臺灣地區國中、國小參與補救教學的學生共2,168人。本研究先進行個別化教學對學習成效直接影響效果的檢測，發現其標準化迴歸係數為 .86，達顯著。進一步分析則發現，部分中介模型優於完全中介模型。故本研究歸納得出的結論為：個別化教學能夠直接影響補救教學學生的學習成效，且個別化教學亦可 透過自我歸因、學習動機等因素，間接影響補救教學學生的學習成效。根據上述結果，本研究提出結論與對教育當局的建議。 The study was commissioned under the contract of the K-12 Education Administration. In this study, 2,168 students in Taiwan who joined the remedial instruction program were randomly selected. A mediation model was applied to analyze the procedure by which individualized teaching influences the learning outcomes of remedial instruction through self-attribution and learning motivation. The analysis results suggested that the direct effect of individualized teaching on the learning outcome was .86. Furthermore, the partial mediation model was more acceptable than the complete mediation model. The results obtained from the partial mediation model are provided as follows: Individualized teaching affected the learning outcomes of low-achieving students who received remedial instruction directly and indirectly through self-attribution and learning motivation. Finally, on the basis of the results, conclusions were drawn, and several policy-making suggestions were proposed for educational authorities in Taiwan.